PENDIDIKAN MULTIKULTURAL DI PESANTREN DALAM MEMBANGUN KARAKTER INKLUSIF - Muhammad Fadli Al Farizi; Adi Prasetyo (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study aims to analyze the role of multicultural education in Islamic boarding schools (pesantren) in building inclusive character. This study uses a qualitative method with a literature study to examine the implementation of multicultural education in strengthening the inclusive character of students in traditional Islamic boarding schools in Indonesia. Data were collected through systematic analysis of relevant literature, including scholarly books, journal articles, and official documents related to pesantren educational models and multiculturalism. The findings reveal that values such as tolerance, cooperation, and respect for cultural identity can be internalized through pesantren cultural practices that emphasize collective decision-making, shared dormitory life, and appreciation of students’ diverse regional backgrounds. The study concludes that multicultural education rooted in pesantren culture contributes significantly to the development of inclusive character by promoting Islamic values of rahmatan lil ‘alamin. The implications highlight the importance of developing multicultural education models that are adaptive to the dynamics of pluralism in Islamic education in Indonesia.